STUDY OF BIOCHEMICAL CHANGES IN KIDNEY AND LIVER FUNCTIONS IN THE BLOOD SERUM OF RATS TREATED WITH DIANABOL - Eidan, Akram Hussein Rahim; awesy, Mohammed Abdulamer dayan; khalel , Amna ghanam ahmad; Shaalan , Teeba Taha Abd; Touma, Samah Hadi Khalibis (Journal of Medical Genetics and Clinical Biology, 2024)
The current study aimed to reveal the cytogenetic effects of Methandienone in white mice Mus Musculus, which is widely used in gyms, by studying some blood images through tests by choosing a third of the dose (0.8) mg/kg of the body weight of the laboratory mouse. The results showed that the increase in the drug has the ability to produce _____ white blood cells and ___ red blood cells at an equal rate. In conclusion, the results of this study show that the drug has mutagenic effects.